Physical Activity And Cardiovascular Risk Factors Among Malays In Selected Rural And Urban Communities In Sarawak - Cheah, W.L; Helmy, Hazmi; Chang, C.T; Wan Manan, Wan Muda (Malaysian Public Health Physicians' Association, 2015)
The objective of this study was to describe the differences in physical activity with socio-demographic factors and its association with cardiovascular risk factors. It was a cross-sectional study among selected urban and rural Malays communities in Kuching and Samarahan. Physical activity data was obtained using International Physical Activity Questionnaire (IPAQ) short version. Assessment of cardiovascular risk factors was based on blood pressure, fasting cholesterol and glucose and body mass index (BMI). Data was analysed using SPSS version 20. A total of 223 participated with higher response from rural areas (60.1%) and females (61.9%). More than half of the respondents (58.5%) were overweight and obese, with a mean BMI of 25.9 kg/m2 (SD=4.9). About 25% of the respondents were found to have blood pressure in the at-risk range. The prevalence of at-risk blood glucose was 52.3% with a mean value of 7.3mmol/L (SD=3.46). The prevalence of at-risk cholesterol were lower with 31.8%, mean value of 3.5 mmol/L (SD=2.94). There were more active respondents living in rural area (p=0.02). Logistics regression analysis showed that urban area (OR=1.988 95% CI 1.082 to 3.652), systolic blood pressure (OR1.020 95% CI 1.003 to 1.037) and blood cholesterol (OR0.884 95% CI 0.785 to 0.996) were associated with physical activity level. Change of physical activity due to urbanization can increase the risk of obesity and other chronic diseases. Efforts to include physical activity in intervention programme should be more intensified, with more provision of suitable built environment.